Challenges and Prospects of STIA LAN Polytechnic Under Government Regulation No. 57 of 2022 - Gedeona, Hendrikus; Purba, Caesar Octoviandy (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
The existence of Government Regulation Number 57 of 2022 concerning the Implementation of Higher Education under Other Ministries and LPNK is not only an important legal basis for the STIA LAN Polytechnic but also a shock effect that is quite worrying for the STIA LAN Polytechnic. Therefore, a critical analysis is carried out using the content analysis method in a qualitative approach to provide an idea for finding solutions related to this policy. Based on the results of the analysis with four important aspects, namely the suitability of the study program with the tasks and functions of LAN RI, the suitability with the national priority program from LAN RI to meet the needs of the job market, technical and specific and not overlapping with the existing study programs in PTN and PTS in one region, it was found that the existence of the STIA LAN Polytechnic is continuing with the roadmap that must be taken, namely making adjustments to existing study programs with the tasks and functions of LAN RI.